KINERJA TERMAL SERAMBI PADA ARSITEKTUR VERNAKULAR KASUS STUDI: MUSEUM NILA DI PROVINSI RIAU - Arman Susilo,; Eddy Prianto , (Nature: National Academic Journal of Architecture, 2023)
The Sang Nila Utama museum building is a vernacular architectural form of traditional buildings that have changed from Riau Malay architecture. This shape change certainly affects the thermal performance of the building itself, which in turn will lead to thermal comfort. Comfort is influenced by a) temperature (oC), b) relative humidity (%), c) wind speed (m/s), and d) MRT (mean radiant temperature). This study aims to determine the thermal performance of the building corridor in terms of spatial climatic factors on temperature and humidity. The method used in this study is a quantitative descriptive correlation, measuring variables of temperature and humidity in the museum corridor and interior. The results of research on the temperature variable in 2 (two) days showed a deasedecreasehe the average thermal performance of the microclimate on the porch of 0.2%, which was shown from the + (positive) value, and from the porch to the interior, there was an increase of 1%, which was shown from the value - (negative). From the average value of the temperature variable, the museum is out of a comfortable condition according to SNI T-14-1993-03.